PROFESSIONAL COMMITMENT OF TEACHER EDUCATORS IN COLLEGES OF EDUCATION IN JAMMU DISTRICT (J&K) Mr. RAMZAN ALI - Mr. RAMZAN ALI (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The major purpose of this research was to understand the professional commitment among teacher educators teaching in the colleges of education in Jammu district of union territory of J&K. The data were collected from 110 teacher educators consisting sex-wise, locality-wise, qualification-wise, NET non-NET-wise, maritalstatus-wise. The random sampling technique was used data. In the present study, Professional Commitment scale for teacher educators (PCSTE) prepared by Dr. Vishal Sood (2011).The tool used was a standardized tool and the collected data were subjected to Mean, Standard Deviation, Standard Error of Mean, Standard Error of Mean Difference, and Correlation. The results of the study indicate that, The Female teacher educators teaching in colleges of education of Jammu district are betters than the Male teacher educators. The M.Phil., Ph.D. teacher educators teaching in colleges of education of Jammu district are better as compared to teacher educators who have only post-graduation degree.The Urban teacher educators teaching in colleges of education of Jammu district are betters as compared to teacher educators of Rural area.The Unmarried teacher educators teaching in colleges of education of Jammu district are better than the married teacher educators.The Net Qualified teacher educators teaching in colleges of education of Jammu district are betters than the Non NET qualified Teacher Educators.